Occupational Hazards among Healthcare Workers in Africa: A Systematic Review - Sarah Mossburg; Angela Agore; Manka Nkimbeng; Yvonne Commodore-Mensah (Ubiquity Press, 2019)
Background: While all healthcare workers are exposed to occupational hazards, workers in sub-Saharan Africa have higher rates of occupational exposure to infectious diseases than workers in developed countries. Identifying prevalence and context of exposure to blood and bloodborne pathogens may help guide policies for prevention. Objective: This systematic review examined occupational exposure rates to blood and bloodborne pathogen among healthcare workers in sub-Saharan Africa. Methods: In November 2017, a comprehensive literature search was conducted to identify studies reporting exposure of health workers in African coutnries to blood and bodily fluids. Title, abstract and full text screening were used to narrow our search. Studies more than 10 years old, or published in non-English languages were excluded. Findings: Fifteen studies reported a variety of exposures. The lifetime prevalence of needlestick injury ranged from 22-95%, and one-year prevalence ranged from 39-91%. Studies included a range of descriptive statistics of knowledge, attitudes, practice and access factors related to exposures. Two studies reported 21-32% of respondents linked poor knowledge or training with prevention of needlestick injuries. Rates of recapping needles ranged from 12-57% in four studies. Attitudes were generally positive toward occupational safety procedures while access was poor. Conclusions: The high burden of blood and bloodborne pathogen exposures demonstrated here indicates a high risk for contracting bloodborne illnesses. Although the data are sparse, implementation of preventative policies based on current knowledge remains critical to minimize risk and reduce exposure. There remains a pressing need for high quality data on occupational hazards to identify the burden of exposures and inform preventive policies in Sub-Saharan Africa. Additional studies are needed to determine whether differential exposures exist between professions and the associations with knowledge, attitudes, practices, and access factors to create targeted strategies to diminish occupational hazards.